Research participation registers can increase opportunities for patients and the public to participate in health services research. (July 2016) - Leach, Verity; Redwood, Sabi; Lasseter, Gemma; Walther, Axel; Reid, Colette; Blazeby, Jane; Martin, Richard; Donovan, Jenny
Members of the public and patients repeatedly indicate their willingness to take part in research, but current United Kingdom research governance involves complex rules about gaining consent. Research participation registers that seek consent from participants to be approached about future studies have several potential benefits, including: increased research participation across clinical and healthy populations; simplified recruitment to health care research; support for people's autonomy in decision making; and improved efficiency and generalizability of research. These potential benefits have to be balanced against ethical and governance considerations. With appropriate processes in place, seeking prospective consent from patients and members of the public to be approached about future studies could potentially increase public participation in health research without compromising informed consent and other ethical principles.